Currículo por tema como alternativa ao curriculo dos cursos de graduação em administração - Monteiro Junior, Sady (1995)
This text refers to a field research about Undergraduate Curriculum of Business Administration that was carried out in three stages. The first stage was conducted to find out how the practice of management or administration was programing, how the target group's academic formation integrating elements had been established, what evaluation the interviewed people made about the courses and which proposals they would present for the curriculum. The second stage answered questions about the intersubjectivity of social sciences, the indispensable qualities to the manager and the important information for constructing ideas, pursuing a proposal of an alternative curricular design to the Traditional Curriculum. The last stage aimed at studying the possibility of an effective introduction of curricular options, exclusively, by emphasazing the proposal of what was called Curriculum by Theme, sufficiently simplified, where the intersubjectivity intercessions appeared in vertically by modules and the intermodular intercessions were made in horizontally by subjects. It is believed that such intercessions would help the students in building their necessary structure to acquire their own knowledge, in order to create habits of taking illations, making comparisons, coming to conc1usions, analysing the facts critically and having a global vision of the phenomenon they are studying. These intercessions could further help them in global comprehension of problems regarding the environment where they live.